Comparative Analysis of Essential Oils from Myrtus communis Berry Color Morphs from Southern Iran - Shahbazian, Donya; Karami, Akbar; Eshghi, Saeid (Natural Products Journal, The, 2018)
Background: Myrtle (Myrtus communis L.) an industrial medicinal plant which belongs to Myrtaceae family with various pharmacological, cosmetic and food applications. Objective: In the current study, variability in leaves Essential Oil (EO) composition of dark blue and white fruited morphs of myrtle populations collected from the same site in the south of Iran, was investigated. Method: The yield of the EO of myrtle morph populations ranged from 0.32% in Zanjiran White (ZFW) to 1.13% in Atashkedeh White (AFW) based on dry weight. According to GC-MS analysis, the chemical composition of myrtle EOs recognized classifying 47 compounds. Result: The major compounds were α-pinene (37.9-70.40%), 1,8-cineole (6.72-28.69%), linalool (0.11- 17.9%), and geraniol (t-6.42%). The most of the recognized compounds showed high chemical difference among myrtle populations. The dark blue morph belonging to Zanjiran dark Blue (ZFB) have the highest amount of α-pinene (70.40%). For 1,8-cineol the highest amount belonged to white morph ZFW (28.69%) and the lowest value belonged to dark blue morph ZFB (6.72%), respectively. Linalool as the same of 1,8-cineol showed a high chemical difference among the myrtle morphs. For linalool, the lowest and highest amounts were obtained in ZFW (0.11%) and Khergheh dark Blue (KFB) about 17.9%, respectively, while geraniol ranged from trace amount in ZFB to 6.42% in AFW populations. Conclusion: Limonene has not shown chemical difference among the myrtle morphs. The results of this investigation indicated that these Myrtus morphs could be a good genetic resource for the high percentage of α-pinene, 1, 8-cineole and linalool as valuable compounds.
Keywords: dark blue and white fruited morphs